Bahaya Kumpul Kebo Bagi Para Pemuja Cinta - Angelline Putri Permatasari; Aris Prio Agus Santoso (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The criminalization of cohabitation is a phenomenon that was recently appointed as a criminal offense in the Draft Criminal Code. Cohabitation, also known as